The Balancing Innovation and Regulation: Legal Protections for Consumers in Indonesia’s Rapidly Expanding E-Commerce Sector - Trisna Dewi, Putu Eka (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 13 No 1 (2024)DO - 10.24843/JMHU.2024.v13.i01.p04, 2024)
E-commerce transactions have a significant role in fostering sustainable economic growth, advancing national development implementation in order to achieve equitable development, and preserving national stability. E-commerce has significant advantages, but it also introduces risk and uncertainty. Consumers are often harmed by e-commerce transaction procedures, which also give rise to a number of legal difficulties. This study employs a statutory approach combined with a literature review as a legal research methodology. The Act Number 19 of 2016 concerning amendments to the Act Number 11 of 2008 concerning Information and Electronic Transactions, the Government Regulation Number 71 of 2019 about Operation of Electronic Systems and Transactions, and the Act Number 8 of 1999 about Consumer Protection all regulate consumer protections in E-commerce transactions. The aforementioned rules work to safeguard consumers' rights during business transactions.